IMPLEMENTASI KURIKULUM MERDEKA DAN STRATEGI PEMBELAJARAN AKTIF DALAM MENINGKATKAN KOMPETENSI SISWA DI ERA PENDIDIKAN 4.0 - Zulvia Trinova; Wilda Rizkiyahnur Nasution; Hatta (CV. Lafadz Jaya, 2026)
This study examines the implementation of the Merdeka Curriculum and active learning strategies in enhancing pupils’ competences in the era of Education 4.0. The changing times, characterised by developments in digital technology, demand that the education system produces pupils who are not only academically excellent but also possess critical thinking, creative, collaborative and communication skills, and are able to adapt to change. The Merdeka Curriculum is a policy that provides educational institutions and teachers with the flexibility to design learning experiences tailored to pupils’ needs, whilst active learning strategies encourage pupils’ direct involvement in the learning process through discussion, projects, problem-solving and collaboration. This study employs a literature review method, examining various relevant sources including books, journal articles and educational policy documents. The findings indicate that the implementation of the Merdeka Curriculum, supported by active learning, is capable of enhancing pupils’ competencies across the board, in terms of knowledge, skills and character. Consequently, the synergy between the Merdeka Curriculum and active learning strategies constitutes an effective approach to addressing the challenges of Education 4.0.